Using Seismic Data and Slip Tendency to Estimate Paleostress: A Case Study From Xicaogu Area of Bohai Bay Basin, China - Ping, Guidong; Liu, Xin; Li, Minghui; Zhang, Xuan; Gao, Yuting; Wang, Sheng; Liu, Xiaobo (Frontiers in Earth Science, 2022)
Paleostress plays an important role in controlling the formation and distribution of reservoir fractures, which is a key factor controlling the production of oil and gas from unconventional reservoirs. At present, there are many methods to perform paleostress inversion, but these methods are mainly based on outcrop or directional core data, which are not easily available in the oil and gas industry, which mainly focuses on the study of underground geological structures. In this study, we use 3D seismic reflection data for the first time to perform slip-tendency-based stress inversion to determine the stress field of the Xicaogu area in the Bohai Bay Basin during the Neogene period. This slip-tendency-based stress inversion method is based on the analysis of slip tendency and fault throw and does not require the measurement of slip directions. The data for this method can easily be extracted from data sets routinely used in the oil and gas industry. The inversion results show that in the study area and the strata of interest, the maximum principal stress axis (σ1) is oriented vertically, the intermediate principal stress axis (σ2) is oriented N70o, the minimum principal stress(σ3) is oriented N160o, and σ2/σ1=0.69 and σ3/σ1=0.27. The results of this study serve as an important reference to clarify fault reactivation at the critical stage of hydrocarbon accumulation.